Clopidogrel Resistance: Current Issues (Journal of Enam Medical College, 2016)
Antiplatelet agents are mainly used in the prevention and management of atherothrombotic complications. Dual antiplatelet therapy, combining aspirin and clopidogrel, is the standard care for patients having acute coronary syndromes or undergoing percutaneous coronary intervention according to the current ACC/AHA and ESC guidelines. But in spite of administration of dual antiplatelet therapy, some patients develop recurrent cardiovascular ischemic events especially stent thrombosis which is a serious clinical problem. Antiplatelet response to clopidogrel varies widely among patients based on ex vivo platelet function measurements. Clopidogrel is an effective inhibitor of platelet activation and aggregation due to its selective and irreversible blockade of the P2Y12 receptor. Patients who display little attenuation of platelet reactivity with clopidogrel therapy are labeled as low or nonresponders or clopidogrel resistant. The mechanism of clopidogrel resistance remains incompletely defined but there are certain clinical, cellular and genetic factors including polymorphisms responsible for therapeutic failure. Currently there is no standardized or widely accepted definition of clopidogrel resistance. The future may soon be realised in the routine measurement of platelet activity in the same way that blood pressure, cholesterol and blood sugar are followed to help guide the therapy, thus improving the care for millions of people. This review focuses on the methods used to identify patients with clopidogrel resistance, the underlying mechanisms, metabolism, clinical significance and current therapeutic strategies to overcome clopidogrel resistance.J Enam Med Col 2016; 6(1): 38-46